Implementasi Program Parenting bagi Orang Tua Siswa di PAUD Al-Akram Desa Sepapan Kabupaten Lombok Timur - Suharyani Suharyani; Ni Ketut Alit Suarti; I Wayan Tamba; I Made Gunawan; Farida Herna Astuti (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this community service program is to assist the managers and teachers of PAUD Al Akram in maximizing 6 aspects of child development, namely aspects of religious and moral values, physical and motoric aspects, cognitive aspects, social emotional aspects, language aspects and art aspects found in students. through the implementation of parenting programs for parents. This service method uses mentoring and counseling with the target being the managers and teachers of PAUD Al-Akram. The result of this service program is that after 6 months of mentoring to managers and teachers, Al Akram PAUD already has a routine schedule of once every 2 weeks for parenting activities for parents of students with parenting material plans that are quite systematic and structured using a learning approach. adults and according to the character of the local community.